SENTRA OLEH-OLEH DI PAGATAN - Amalia, Nur Samsiah; Muchamad, Bani Noor (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
The number of visits and tourist attractions in Pagatan Regency, Tanah Bumbu is increasing every year. One of the needs that will influence the increase in tourists in the area is the need for souvenir centers. Based on data in the field, the existence of souvenir centers is not well organized, the existing souvenir shops are still scattered with different types of products in each shop so that tourists need a lot of time to look for souvenirs. So there is a need for a souvenir center that can accommodate shopping needs in one place as an educational place and can display the characteristics of the Pagatan Tanah Bumbu area through its visual appearance. This is in line with the concept promoted, namely one stop shopping. To realize this plan, the Neo-vernacular architectural approach concept of the Tanah Bumbu traditional house was used. The application of this house is to adopt the roof shape of the Tanah Bumbu traditional house, namely using a shield roof.